Evaluation of the Association of Polymorphisms With Palbociclib-Induced Neutropenia: Pharmacogenetic Analysis of PALOMA-2/-3. (7th June 2021) - Iwata, Hiroji; Umeyama, Yoshiko; Liu, Yuan; Zhang, Zhe; Schnell, Patrick; Mori, Yuko; Fletcher, Olivia; Marshall, Jean-Claude; Johnson, Jillian G.; Wood, Linda S.; Toi, Masakazu; Finn, Richard S.; et al.
Abstract: Background: The most frequently reported treatment-related adverse event in clinical trials with the cyclin-dependent kinase 4/6 (CDK4/6) inhibitor palbociclib is neutropenia. Allelic variants in ABCB1 and ERCC1 might be associated with early occurrence (i.e., end of week 2 treatment) of grade 3/4 neutropenia. Pharmacogenetic analyses were performed to uncover associations between single nucleotide polymorphisms (SNPs) in these genes, patient baseline characteristics, and early occurrence of grade 3/4 neutropenia. Materials and Methods: ABCB1 (rs1045642, rs1128503) and ERCC1 (rs3212986, rs11615) were analyzed in germline DNA from palbociclib-treated patients from PALOMA-2 ( n = 584) and PALOMA-3 ( n = 442). SNP, race, and cycle 1 day 15 (C1D15) absolute neutrophil count (ANC) data were available for 652 patients. Univariate and multivariable analyses evaluated associations between SNPs, patient baseline characteristics, and early occurrence of grade 3/4 neutropenia. Analyses were stratified by Asian ( n = 122) and non-Asian ( n = 530) ethnicity. Median progression-free survival (mPFS) was estimated using the Kaplan-Meier method. The effect of genetic variants on palbociclib pharmacokinetics was analyzed. Results: ABCB1 and ERCC1 _rs11615 SNP frequencies differed between Asian and non-Asian patients. Multivariable analysis showed that low baseline ANC was a strong independent risk factor for C1D15 grade 3/4 neutropenia regardless of race (Asians: odds ratio [OR], 6.033, 95% confidence interval [CI], 2.615−13.922, p < .0001; Non-Asians: OR, 6.884, 95% CI, 4.138−11.451, p < .0001). ABCB1 _rs1128503 (C/C vs. T/T: OR, 0.57, 95% CI, 0.311−1.047, p = .070) and ERCC1 _rs11615 (A/A vs. G/G: OR, 1.75, 95% CI, 0.901−3.397, p = .098) were potential independent risk factors for C1D15 grade 3/4 neutropenia in non-Asian patients. Palbociclib mPFS was consistent across genetic variants; exposure was not associated with ABCB1 genotype. Conclusion: This is the first comprehensive assessment of pharmacogenetic data in relationship to exposure to a CDK4/6 inhibitor. Pharmacogenetic testing may inform about potentially increased likelihood of patients developing severe neutropenia (NCT01740427, NCT01942135). Implications for Practice: Palbociclib plus endocrine therapy improves hormone receptor–positive/human epidermal growth factor receptor 2–negative advanced breast cancer outcomes, but is commonly associated with neutropenia. Genetic variants in ABCB1 may influence palbociclib exposure, and in ERCC1 are associated with chemotherapy-induced severe neutropenia. Here, the associations of single nucleotide polymorphisms in these genes and baseline characteristics with neutropenia were assessed. Low baseline absolute neutrophil count was a strong risk factor ( p < .0001) for grade 3/4 neutropenia. There was a trend indicating that ABCB1 _rs1128503 and ERCC1 _rs11615 were potential risk factors ( p < .10) for grade 3/4 neutropenia in non-Asian patients. Pharmacogenetic testing could inform clinicians about the likelihood of severe neutropenia with palbociclib. Abstract : The most frequently reported treatment-related adverse event in clinical trials with the cyclin-dependent kinase 4/6 (CDK4/6) inhibitor palbociclib is neutropenia. In this study, pharmacogenetic analyses were performed to uncover associations between single nucleotide polymorphisms in the ABCB1 and ERCC1 genes, patient baseline characteristics, and early occurrence of grade 3/4 neutropenia.